The future of management : entrepreneurship, change and flexibility - Buła, Piotr; e (Krakow : Jagiellonian University Press, 2019)
We believe that the world is standing on the very edge of the fastest industrial revolution ever. A revolution which will rapidly increase the efficiency of many production processes. Automation (both mechanical and the one happening with computer processes) will reduce the demand for human work and release a huge amount of time we can use for further development. With this book we try to provide the reader with information about various aspects of life and the socio-economic environment. For this purpose, we have invited authors representing the leading scientific research centers in Poland and specialists from foreign universities.' Piotr Bula Bogdan Nogalski 'The monograph stands out from the publications related to change management in the context of entrepreneurial opportunities and flexibility of the organization. The authors attempt to integrate retrospective and prognostic approaches, so they not only assess the current status, but also point to challenges for management science. The work has been prepared by scholars whose authority in management sciences is undisputed. I positively assess the empirical and methodological layer of individual chapters of the monograph. Discussing the results of their scientific and research work, the authors presented the determinants of management processes described from the perspective of entrepreneurial opportunities and flexibility of the organization.' Szymon Cyfert
Title from publisher's bibliographic system (viewed on 19 Nov 2021).
Keywords: Industrial management